Magnetic meridional winds in the thermosphere obtained from Global Assimilation of Ionospheric Measurements (GAIM) model. Issue 9 (21st September 2015) - Lomidze, Levan; Scherliess, Ludger; Schunk, Robert W.
Abstract Thermospheric neutral winds play an important part in the dynamics of ionospheric plasma and represent one of the key inputs for ionospheric physics‐based models. Yet wind measurements are scarce and generally lack global coverage and continuity. To help mitigate this shortcoming, a data assimilation model was used to estimate neutral winds in the low‐ and middle‐latitude thermosphere. Seasonal global maps of NmF2 and hmF2 were generated from Constellation Observing System for Meteorology, Ionosphere, and Climate radio occultation measurements for geomagnetically quiet and low solar flux conditions. The maps were assimilated into the Utah State University Global Assimilation of Ionospheric Measurements–Full Physics (GAIM‐FP) model. GAIM‐FP, which uses the physics‐based ionosphere‐plasmasphere model (IPM) and employs an ensemble Kalman filter technique, significantly improved the agreement between the modeled and measured NmF2 and hmF2 globally compared to the IPM. Global quiet time magnetic meridional winds were derived for December and June solstices and March equinox. The morphology of the derived winds was analyzed and validated by comparing with ground‐based measurements and with wind values from the empirical horizontal wind model. GAIM‐FP‐estimated winds were shown to be in good agreement with the wind observations. Furthermore, the sensitivity of the derived winds to uncertain parameters, including the O+‐O collision frequency, neutral composition, number of radio occultations, and data errors, was investigated. The uncertainties were found to have only small effects on the derived winds. The results of this work indicate that thermospheric wind estimation from GAIM‐FP is a valuable tool for wind specification over regions where limited or no wind measurements exist.